PENERAPAN KEPEMIMPINAN ADAPTIF DALAM MENGELOLA PERUBAHAN KURIKULUM PESANTREN DI ERA DIGITAL - Hariyadi, Ahmad; Annasih, Sa'aduddin; Fathurohman, Irfai; Wijayanto, Wasis; Fajrie, Nur (Equity In Education Journal, 2024)
This study analyzes the application of adaptive leadership in managing changes in the pesantren curriculum in the digital era. Islamic boarding schools are faced with the challenge of adapting the curriculum to technological developments and the needs of the younger generation. Adaptive leadership is important in facing these challenges, emphasizing flexibility, participation, and innovation. The research uses a descriptive qualitative approach, with data obtained from interviews, observations, and documentation studies at the Kauman Lasem Islamic Boarding School, Rembang. Data sources include pesantren leaders, administrators, teachers, and documents related to the curriculum. The data was analyzed by reduction and triangulation techniques. The results show that the implementation of adaptive leadership involves three main steps: identifying the need for change, developing a technology-based curriculum, and strengthening collaboration between stakeholders. Adaptive pesantren leaders build a participatory culture and encourage innovation through the integration of technology in learning.